Introversion - extroverstion factors and the ESL proficiency (listening and speaking) level of UiTM Melaka students - Norfazlika binti Abd. Karim (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2010)
A few numbers of studies have been done in educational psychology concerning English as a Second Language (ESL) subject proficiency in relation to introversion – extroversion (INT – EXT) factors. However, quite a number of those studies reveal almost an unclear pattern of either negative or positive link between the two variables. Such beliefs that INT – EXT may help or hinder developing English as a second / foreign language skills may be only half-truth for some researchers but those beliefs undoubtedly provide the stimulus for systematic investigations. Having been provided with such a stimulus, the researcher investigated if INT – EXT factors are related to ESL subject proficiency. That is, an examination of correlation between INT – EXT factors of eighty-two bumiputera first year second semester diploma students of office management, mass communication and art and design major from the Universiti Teknologi MARA (UiTM) Melaka extensive program; Preparatory Course for MUET (BEL 260) and the two ESL subject proficiency groups; listening and speaking, controlling for gender and academic course. Data relevant to this study was collected through three instruments; the Student Information Questionnaire, Eysenck Personality Quiz (EPQ) and UiTM Standardized Listening and Speaking Proficiency Tests. The major result obtained by the researcher showed that no statistically significant predictive relationship existed between personality type and ESL subject proficiency. However, the other results of running a one-way ANOVA showed statistically significant mean differences between: 1) academic course and INT – EXT and 2) academic course and speaking proficiency. In sum, the data of the present study suggests that the academic and intellectual problems dealing with whether (and to what extent) relationships between personality and proficiency within an ESL framework exist are certainly not closed. Indeed, the aforementioned results indicate a need for future research which more closely examines the relationship between INT – EXT and ESL subject proficiency.